Foamability and viscosity behavior of extrusion foamed PLA–pulp fiber biocomposites. Issue 41 (8th July 2019) - Rokkonen, Teijo; Peltola, Heidi; Sandquist, David
ABSTRACT: This study addresses the effect of fiber reinforcement, chain extension, and physical foaming agent type on foam morphology and viscosity behavior of pulp fiber reinforced poly(lactic acid) (PLA) biocomposites. PLA reinforced with 0, 10, and 20 wt % of bleached kraft pulp fibers with and without chain extender were foamed using two different physical foaming agents (carbon dioxide and isobutane) by extrusion foaming. Densities, foam morphologies, and viscosities were systematically analyzed and compared from the produced foams. As a conclusion, low‐density foams are produced with both foaming agents and fiber levels, fiber addition limiting cell growth. Isobutane provides better dimensional stability with narrower cell size distribution, whereas carbon dioxide enables lower foaming temperature. Chain extension is essential to achieve foam with low density and good cell structure. Contrary to nonchain extended PLA, addition of fibers reduced the viscosity of chain extended PLA. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48202. Abstract :